Outcomes after resection of leiomyosarcomas of the inferior vena cava: A pooled data analysis of 377 cases. (March 2015) - Wachtel, Heather; Gupta, Meera; Bartlett, Edmund K.; Jackson, Benjamin M.; Kelz, Rachel R.; Karakousis, Giorgos C.; Fraker, Douglas L.; Roses, Robert E.
Abstract Background Primary leiomyosarcomas of the inferior vena cava (IVC) pose unique surgical challenges. Due to the rarity of the disease, little definitive data exists on prognosis and treatment options. Methods A pooled data analysis was performed on all cases of initial IVC leiomyosarcoma resection identified by literature search (n = 371) and our institutional database (n = 6). Kaplan–Meier and Cox regression analyses were performed to identify factors associated with disease-free survival (DFS) and overall survival (OS). Results Patients were predominantly female (76%, n = 286); the median age of presentation was 55 years. Five-year DFS and OS were 6% and 55%, respectively. Preoperative factors independently associated with decreased OS included older age (HR:1.05, 95% CI:1.00–1.09), larger tumor size (HR:1.14, 95% CI:1.04–1.24), resection of adjacent organ(s) (HR:3.62, 95% CI:1.34–9.77), and R2 resection (HR:7.80, 95% CI:1.94–32.05). Isolated involvement of the suprarenal infrahepatic IVC was associated with longer OS (HR:0.22, 95% CI:0.06–0.78). A scoring system incorporating independent predictors of OS stratified outcomes: score 4–5 (n = 10, median OS 6 months), score 2–3 (n = 88, median OS 23 months) compared to a score of 0–1 (n = 44, median OS 29 months). Conclusions Following resection of IVC leiomyosarcomas, recurrence is a near certainty; long-term survival, however is possible. The dominant predictors of survival include margin status, tumor size and radical resection. These can be combined into a risk score that has prognostic value.